Software Development to Calculate Absorbed Dose Rate Distribution Using TG-43 Formula - Ismet Isnaini; Wahyuni Z Imrana (Indonesian Journal of Pharmaceutical Science and Technology, 2019)
Radioisotope applications have become widespread in many fields, such as medical. For the optimal treatment using radioisotope, an accurate absorbed dose rate distribution calculation is required to provide the optimal dose for each patient. A software has been designed to calculate this absorbed dose rate distribution so that paramedics would know whether the absorbed dose rate distribution emitted from that particular source is sufficient or not. Using the TG-43 formula derived by American Association of Physicist in Medicine (AAPM), the calculation were performed using manufacturing data of the Ir-192 source and the function which involve the geometric position between the source and a calculation point. The results of this calculation which were viewed using the imageJ software, have shown that the absorbed dose rate for a source located in the center of  a volume was getting larger near the source location but has decreased drastically at the source location.This is due to the unavailability of manufacturing data for radius less than 2.5 mm. As for absorbed dose rate distribution emitted from several sources, the dose rate accumulated and reached the maximum in the middle. It has also formed some sort of shape depending on the location of the source, which form an isodose line or curves.Keywords: TG-43 Formula, absorbed dose rate distribution